2008
DOI: 10.1103/physrevb.77.014412
|View full text |Cite
|
Sign up to set email alerts
|

O17andV51NMR for the zigzag spin-1 chain compoundet al.

Abstract: Abstract51V NMR studies on CaV 2 O 4 single crystals and 17O NMR studies on 17O-enriched powder samples are reported. The temperature dependences of the 17O NMR linewidth and nuclear spin-lattice relaxation rate give strong evidence for a long-range antiferromagnetic transition at T N =78 K in the powder. Magnetic susceptibility measurements show that T N =69 K in the crystals. A zero-field 51V NMR signal was observed at low temperatures (f≈237 MHz at 4.2 K) in the crystals. The field-swept spectra with the fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 14 publications
4
42
2
Order By: Relevance
“…10,11 In single crystals, at temperatures below 45 K we do find a zero-field 51 V NMR signal where the 51 V nuclei resonate in the static component of the local magnetic field generated by the long-range AF order below T N Ϸ 70 K. 14 The ordered moment at 4.2 K in the crystals was estimated from the zero-field 51 V NMR measurements to be 1.3͑3͒ B / ͑V atom͒, somewhat larger than but still consistent with the value 1.06͑6͒ B / ͑V atom͒ from the above neutron diffraction measurements. 13 An energy gap ⌬ for antiferromagnetic spin wave excitations was found with a value ⌬ / k B =80͑20͒ K in the temperature range of 4-45 K, where k B is Boltzmann's constant.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…10,11 In single crystals, at temperatures below 45 K we do find a zero-field 51 V NMR signal where the 51 V nuclei resonate in the static component of the local magnetic field generated by the long-range AF order below T N Ϸ 70 K. 14 The ordered moment at 4.2 K in the crystals was estimated from the zero-field 51 V NMR measurements to be 1.3͑3͒ B / ͑V atom͒, somewhat larger than but still consistent with the value 1.06͑6͒ B / ͑V atom͒ from the above neutron diffraction measurements. 13 An energy gap ⌬ for antiferromagnetic spin wave excitations was found with a value ⌬ / k B =80͑20͒ K in the temperature range of 4-45 K, where k B is Boltzmann's constant.…”
Section: Introductionmentioning
confidence: 78%
“…As discussed in Sec. I, our recent NMR and magnetic neutron diffraction experiments on single crystal CaV 2 O 4 indicated that the magnetic structure at 4 K is noncollinear, 14,15 which can at least partially explain the nonzero spin susceptibility along the ͑average͒ easy b axis at low temperatures. In addition, the reduction in the local ordered moment ͑1.0-1.6͒ B / ͑V atom͒ of the ordered vanadium spins found in these studies from the expected value gS B =2 B / ͑V atom͒ suggests that quantum zero-point spin fluctuations could be strong and could contribute to the large finite b spin ͑T → 0͒.…”
Section: Magnetic Susceptibilitymentioning
confidence: 99%
“…The Ca atoms are located in between these chains. The system undergoes an orthorhombic to monoclinic structural distortion at a sample-dependent T S ≈ 108 − 145 K and an antiferromagnetic transition with noncollinear spin structure at a sample-dependent T N ≈ 50 − 70 K. [40][41][42] A peak in the heat capacity versus temperature at T ∼ 200 K has been observed which might be the long-sought chiral phase transition. A detailed study involving synthesis of polycrystalline and single crystal samples of CaV 2 O 4 , and investigation of magnetic, structural, and thermal properties of the samples, is given in Appendix A of this thesis.…”
Section: High Pressure Powder X-ray Diffraction On LIV 2 O 4 Crystalsmentioning
confidence: 99%
“…[40,41] This unusual magnetic susceptibility provided us with a strong motivation to further study this class of materials and the results are described in Ch. 7 of this thesis.…”
Section: High Pressure Powder X-ray Diffraction On LIV 2 O 4 Crystalsmentioning
confidence: 99%
See 1 more Smart Citation